Subnational debt of China: The politics-finance nexus - Gao, Haoyu; Ru, Hong; Tang, Dragon Yongjun (Journal of Financial Economics, 2021)
We provide direct evidence that governments selectively default on debt when they can identify creditors. Analyzing a comprehensive data set of subnational debt, we show that Chinese local governments choose to default on banks with weaker political power. A reduction in a bank's political power relative to other banks increases the likelihood of selective default by local governments. Such default selections are driven by banks’ influence over politician promotion. When local politicians are highly ranked or connected to national leaders, they engage less in selective default as their promotion is less affected by bank loan defaults. Our findings suggest a politics-finance nexus through which government defaults are restrained.